Human Three-Dimensional Hepatic Models: Cell Type Variety and Corresponding Applications - Xu, Qianqian (Frontiers in Bioengineering and Biotechnology, 2021)
Owing to retained hepatic phenotypes and functions, human three-dimensional (3D) hepatic models established with diverse hepatic cell types are thought to recoup the gaps in drug development and disease modeling that limited by conventional two-dimensional (2D) cell culture system and species-specific variability in drug metabolizing enzymes and transporters. Primary human hepatocytes, human hepatic cancer cell lines, and human stem cells-derived hepatocyte-like cells are three main hepatic cell types used in current models and exhibit divergent hepatic phenotypes. Primary human hepatocytes derived from healthy hepatic parenchyma resemble in vivo-like genetic and metabolic profiling. Human hepatic cancer cell lines are unlimitedly reproducible and tumorigenic. Stem cells-derived hepatocyte-like cells derived from patients are promising to retain donor’s genetic background. It has been suggested in some studies that unique properties of cell types endue them with benefits in different research fields of in vitro 3D modeling paradigm. For instance, primary human hepatocyte was thought to be the gold standard for hepatotoxicity study, and stem cells-derived hepatocyte-like cells has taken a main role in personalized medicine and regenerative medicine. But comprehensive review focuses on the hepatic cell type variety and corresponding applications in 3D models are sparse. Therefore, this review summarized the characteristics of different cell types and discussed opportunities of different cell types in drug development, liver disease modeling and liver transplantation.